A Plant-Feeding Nematode Indirectly Increases the Fitness of an Aphid - Hoysted, Grace A.; Lilley, Catherine J.; Field, Katie J.; Dickinson, Michael; Hartley, Sue E.; Urwin, Peter E. (Frontiers in Plant Science, 2017)
Plants suffer multiple, simultaneous assaults from above and below ground. In the laboratory, pests and/or pathogen attack are commonly studied on an individual basis. The molecular response of the plant to attack from multiple organisms and the interaction of different defence pathways is unclear. The inducible systemic responses of the potato (Solanum tuberosum L.) host plant were analysed to characterise the plant-mediated indirect interactions between a sedentary, endoparasitic nematode (Globodera pallida) and a phloem-sucking herbivore (Myzus persicae). The reproductive success of M. persicae was greater on potato plants pre-infected with G. pallida compared to control plants. Salicylic acid (SA) increased systemically in the leaves of potato plants following nematode and aphid infection singly with a corresponding increase in expression of SA-mediated marker genes. An increase in jasmonic acid (JA) associated with aphid infection was suppressed when plants were co-infected with nematodes. Our data suggests a positive, asymmetric interaction between a sedentary endoparasitic nematode and a sap-sucking insect. The systemic response of the potato plant following infection with G. pallida indirectly influences the performance of M. persicae. This work reveals additional secondary benefits of controlling individual crop pests.